2004
DOI: 10.1111/j.0014-3820.2004.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Population Sizes and Temporal Stability of Genetic Structure in Rana Pipiens, the Northern Leopard Frog

Abstract: Abstract. Although studies of population genetic structure are very common, whether genetic structure is stable over time has been assessed for very few taxa. The question of stability over time is particularly interesting for frogs because it is not clear to what extent frogs exist in dynamic metapopulations with frequent extinction and recolonization, or in stable patches at equilibrium between drift and gene flow. In this study we collected tissue samples from the same five populations of leopard frogs, Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 65 publications
(70 reference statements)
6
75
0
Order By: Relevance
“…The N e /N ratio estimated for the adult population was 0.086, which again is in the general range of DNA-based estimates for other ranid frogs (Hoffman et al 2004;Schmeller and Merila 2007). Thus, our data are consistent with previous suggestions that N e /N ratios in ranid frogs are in the typical range for vertebrates (e.g., *0.1-0.4), while those for bufonids are much lower (Hoffman et al 2004;Brede and Beebee 2006). Our main objective was to test a hypothesis about what features of the life cycle of R. pretiosa cause N e to be reduced relative to N. By obtaining separate N b estimates using egg and metamorph samples we could determine if these N b estimates differed from each other and from the simple estimate from counting egg massesN ab À Á .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The N e /N ratio estimated for the adult population was 0.086, which again is in the general range of DNA-based estimates for other ranid frogs (Hoffman et al 2004;Schmeller and Merila 2007). Thus, our data are consistent with previous suggestions that N e /N ratios in ranid frogs are in the typical range for vertebrates (e.g., *0.1-0.4), while those for bufonids are much lower (Hoffman et al 2004;Brede and Beebee 2006). Our main objective was to test a hypothesis about what features of the life cycle of R. pretiosa cause N e to be reduced relative to N. By obtaining separate N b estimates using egg and metamorph samples we could determine if these N b estimates differed from each other and from the simple estimate from counting egg massesN ab À Á .…”
Section: Discussionsupporting
confidence: 60%
“…Estimates from these various methods are listed along with their 95% confidence intervals (Bayesian credible intervals for the TL estimates) and N b /N ratios Beebee 2006). The N e /N ratio estimated for the adult population was 0.086, which again is in the general range of DNA-based estimates for other ranid frogs (Hoffman et al 2004;Schmeller and Merila 2007). Thus, our data are consistent with previous suggestions that N e /N ratios in ranid frogs are in the typical range for vertebrates (e.g., *0.1-0.4), while those for bufonids are much lower (Hoffman et al 2004;Brede and Beebee 2006).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Genetic N e /N ratios as low as ours (0.027-0.069), though not common, have been reported for fish (Miller and Kapuscinski 1997) and amphibians (Rowe and Beebee 2004;Easteal 1985;Hoffman et al 2004;Miller and Kapuscinski 1997;Scribner et al 1997 (Waples et al 2013)] are mostly appreciably higher than those of guanacos.…”
Section: Genetic N E and N Bsupporting
confidence: 52%
“…Peltophryne lemur is moderately variable at the six microsatellite loci. Within-population genetic diversity (H E ) is similar to or greater than that found for microsatellite loci in several other amphibians (Rowe et al 1998;Palo et al 2003;Brede and Beebee 2004;Martinez-Solano et al 2005;Arens et al 2006), while only a few have been found to have substantially greater H E (Austin et al 2003;Burns et al 2004;Hoffman et al 2004). Allelic diversity for P. lemur is comparable to several species examined over similar and larger geographical scales, despite much larger sample sizes for some (Rowe et al 1998;Palo et al 2003;Brede and Beebee 2004;Kraaijeveld-Smit et al 2005;Arens et al 2006).…”
Section: Genetic Diversity Within Populationsmentioning
confidence: 74%